1=sec^2(x+y)(1+y')
so, y'=cos^2(x+y)-1
2006-11-01 16:02:31
·
answer #1
·
answered by askance 4
·
0⤊
0⤋
dy/dx = 1+tan(x+y)^2
2006-11-02 00:00:23
·
answer #2
·
answered by Guru 6
·
0⤊
0⤋
Y=1
x= -1
2006-11-02 00:00:51
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
i dun know whether this's right or wrong...
i just do it on my own...
1st, using the division rule : [v(d/dx0u-u(d/dx)v]/v^2
then...
u do the nonsence... n u'll get
=1/cos(x+y)^2.[cos(x+y)dy/dx(cos(x+y)+sin(x+y)dy/dxsin(x+y)]
by factoring the dy/dx,
=1/cos(x+y)^2.[(dy/dx)(cos^2(x+y)+sin^2(x+y))]
we know that,
sin^a+cos^a =1
and,
1/cos^2a=sec^2a,
hence,
simplify the equation, we'll get
=sec^2(x+y)dy/dx
TA-DA!!! ^_^
2006-11-02 01:27:19
·
answer #4
·
answered by azfarbeckham 1
·
0⤊
0⤋
y = atan(x) - x
dy/dx = 1/(1+x^2) - 1
2006-11-02 00:10:24
·
answer #5
·
answered by Helmut 7
·
0⤊
1⤋
dy/dx=-sin²(x+y)
2006-11-02 00:03:52
·
answer #6
·
answered by venomfx 4
·
0⤊
0⤋